Seismic performance of reinforced concrete filled steel tube drilled shafts with inground plastic hinges. (15th June 2018) - Aguirre, D.A.; Kowalsky, M.J.; Nau, J.M.; Gabr, M.; Lucier, G.
Highlights: This manuscript presents the results of an experimental program that included cyclic experimentation on reinforced concrete filled steel tube specimens embedded in soil. The paper also shows details of a finite element analytical model that was used for performance prediction purposes and subsequently calibrated based on the collected experimental data. The force-displacement response, tensile strain distribution, and hysteretic equivalent viscous damping are discussed in this paper. Abstract: The seismic performance of reinforced concrete-filled steel tube (RCFST) drilled shafts, also known as RCFST pile-columns, was examined based on experimental tests conducted on twelve half-scale RCFST specimens at the soil-structure interaction facility at the North Carolina State University, Constructed Facilities Laboratory (NCSU-CFL). The specimens consisted of steel tubes with diameter-to-thickness (D/t) ratios ranging from 48 to 95 that were filled with reinforced concrete. Spirally welded steel tubes with outer diameters (D) of 12″ (305 mm) and 12–3/4″ (324 mm) were utilized. The specimens were tested with aboveground-to-diameter (La /D) ratios of 5.5 and 7.5, and they were embedded 14′ (4270 mm) into poorly graded sand (SP). Different levels of soil stiffness were induced in the sand by using a soil-sandwich approach, which allowed for modifying the soil stiffness profile by means of applying a surcharge on the soil surface. Cyclic lateral load was applied by a 100-kip (445 kN), 70-in. (1780 mm) stroke hydraulic actuator, supported on a braced steel frame, and pin-connected to the pile-column head ensuring that the plastic hinge developed below ground. The failure mechanism was controlled by the tensile strain in the steel tube and it was caused by a combination of tube local buckling and tube fracture. First, tube local buckling developed outward at the extreme compression fiber of the section. Tube fracture then occurred in the section with the largest buckle and it extended around about half of the section perimeter. The plastic hinge developed at depths of 2D to 4D. Onset of tube local buckling was observed at higher displacement ductility levels (µ = 3) for specimens using thicker tubes (D/t = 48) than for those using thinner tubes (D/t = 95). The force-displacement response, tensile strain distribution, and hysteretic equivalent viscous damping are discussed in this paper.